Psychological Well-Being of Working Women Depending on Marital Status - Huliaieva , Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The psychological well-being of Ukrainian women in modern conditions is shaped by the influence of prolonged military operations and is characterized by contradictions and heterogeneity. The transformation of social and family roles, the combination of professional workload with family responsibilities, the presence or absence of partner support, as well as the actualization of life meaning issues , personal growth and self-realization are the main factors shaping women’s psychological well-being. The aim of the study was to determine the characteristics of working women psychological well-being with different family statuses and identify factors that increase or decrease its level. The results showed that marriage, combined with professional employment, acts as a resource factor, contributing to harmonious interpersonal relationships, a positive attitude towards oneself, and control over life circumstances. Married women are focused on maintaining the stability of family and social relationships, while unmarried women are focused on self-expression, external attractiveness, and professional achievements. The psychological well-being of married women is associated with deeper emotional involvement in work and integration of professional and family roles, while in unmarried women it is determined by activity and emotional involvement in professional activities.